The Principal's Role in Encouraging the Use of Quizizz as Interactive Media at SD Negeri 1 Wonosari - Istinganah Istinganah; Jumintono Jumintono; Saryanto Saryanto (CV Edujavare Publishing, 2026)
The rapid development of digital technology has transformed educational practices worldwide, requiring schools to adapt learning processes that are more interactive, engaging, and responsive to students’ diverse needs. This study aims to analyze the causes of reading difficulties among slow learner students, describe the implementation of the Interactive Digital Learning strategy, and examine its effectiveness in improving reading skills at SD Negeri 1 Wonosari. The research employed a qualitative descriptive approach involving observation, interviews, and documentation to collect data regarding the learning experiences of a fourth-grade slow learner student. The findings revealed that reading difficulties were influenced by cognitive limitations, low learning motivation, limited self-confidence, and environmental factors affecting literacy development. To address these challenges, teachers implemented an Interactive Digital Learning strategy utilizing digital media such as PowerPoint, Canva, and educational videos to create engaging and student-centered learning experiences. The implementation process included planning, classroom application, observation, and evaluation to ensure that learning activities met students’ needs. The results demonstrated that Interactive Digital Learning significantly enhanced students’ motivation, participation, confidence, reading fluency, and reading comprehension. The effectiveness of the strategy can be explained through Constructivist Theory, Sociocultural Theory, Multimedia Learning Theory, Self-Determination Theory, and Social Cognitive Theory, which emphasize the importance of active engagement, technological support, and meaningful learning experiences.